2018
DOI: 10.1111/1556-4029.13874
|View full text |Cite
|
Sign up to set email alerts
|

The PEth Blood Test in the Security Environment: What it is; Why it is Important; and Interpretative Guidelines

Abstract: Testing for phosphatidylethanol (PEth) is a relatively new tool for detecting and grossly quantifying a person's use of alcohol in a variety of security, medical, and legal environments. The basic chemistry of PEth is explained with a particular focus on factors that make it highly suitable as a biomarker for alcohol use in such situations. This article meets the need for a literature review that synthesizes PEth laboratory findings and suggests updated guidelines for interpretation. Several ethanol biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(139 citation statements)
references
References 37 publications
3
115
1
6
Order By: Relevance
“…Moreover, there is no established PETH cutoff concentration that is used for assessing PAE in newborns. 27,28 Some researchers have reported values above the limit of detection (LOD, ≥2 ng/ml) to indicate positive PAE, 27 while others have proposed that future research should ascertain if PETH concentration in DBS samples between 2 and 8 ng/ml should be considered as light alcohol use and ≥8 ng/ml should be considered moderate to heavy alcohol use in pregnancy. 12 For this study we used the cutoff of ≥8 ng/ml based on several previous reports suggesting the limit of quantification (LOQ) indicated any alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is no established PETH cutoff concentration that is used for assessing PAE in newborns. 27,28 Some researchers have reported values above the limit of detection (LOD, ≥2 ng/ml) to indicate positive PAE, 27 while others have proposed that future research should ascertain if PETH concentration in DBS samples between 2 and 8 ng/ml should be considered as light alcohol use and ≥8 ng/ml should be considered moderate to heavy alcohol use in pregnancy. 12 For this study we used the cutoff of ≥8 ng/ml based on several previous reports suggesting the limit of quantification (LOQ) indicated any alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…12,14,16,22,23 A previous validation article notes that this cutoff has 100% specificity and lower but comparable sensitivity to other methodologies to detect moderate chronic or intermittent binge drinking patterns during pregnancy. 27 Although some researchers utilize a higher cutoff of ten times the LOD (>20 ng/ml) for identifying late pregnancy PAE, 13,28 this higher cutoff was recommended for liquid blood specimens for the general population and not for the newborn population alone. 22 In liquid blood samples the post-collection synthesis of PETH may occur if ethanol is present in the blood sample, resulting in false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…PEth has recently been introduced as a routine alcohol biomarker to confirm abstinence or detect harmful drinking ( Ulwelling and Smith, 2018 ). However, an important issue for the latter application is that it appears to be difficult to establish the magnitude of alcohol intake based on a PEth value, as several studies have demonstrated considerable variation in test response between different individuals ( Aradottir et al.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research in adults (mostly white males) suggests higher PEth levels are associated with heavier and more frequent alcohol use. A study by Unwellings group suggests PEth levels <80 indicate moderate drinking of 2‐4 drinks several times a week (Unwelling & Smith 2018) and potentially lower FASD risk. In our sample, 33 women and 177 newborns had levels over 80 suggesting significant alcohol exposure in a large group.…”
Section: Discussionmentioning
confidence: 99%